Regulation and Economic Performance Product Market Reforms and Productivity in the OECD - Nicoletti, Giuseppe (OECD Economics Department Working Papers, 2005)
This paper assesses the implications of past and ongoing reforms in OECD product markets for the labour productivity gap, a key component of cross-country differences in GDP per capita. After a brief review of the theoretical literature, we bring together the results obtained in some of our empirical work over the past few years, discussing econometric approaches and their drawbacks. We then use these results to gauge the likely effect of further reforms. We distinguish effects on capital deepening and technical progress by examining the impact of regulations on investment (domestic and foreign) and multi-factor productivity. We focus on the effects of policies aimed at strengthening private governance (e.g. through privatization) and opening up access to markets where competition is economically viable. The results suggest that pro-competitive reforms tend to increase both investment and multifactor productivity and, through both these channels, they can lead to higher growth in GDP per capita